Morphological and Genetic Recovery of Coral Polyps After Bail-Out - Chuang, Po-Shun; Ishikawa, Kota; Mitarai, Satoshi (Frontiers in Marine Science, 2021)
Contemporary advances in microfluidic and molecular techniques have enabled coral studies to shift from reef and colony scales to polyp- and molecular-level investigations. Polyp bail-out provides an alternative approach to acquire solitary polyps for studies at finer scales. Although induction of polyp bail-out has been reported in several studies, polyp health after bail-out has not been investigated. In this study, we monitored morphological and genetic changes in Pocillopora acuta polyps after bail-out induced by hyperosmosis. In isosmotic conditions, over 80% of bailed-out polyps survived, of which half regenerated normal polyp morphology within 5 days, including a polarized polyp body, extended tentacles, and a distinguishable oral disk. In contrast, the remaining polyps degenerated into tissue ball-like structures that resemble multicellular aggregates reported in earlier studies. In morphologically recovered polyps, transcriptomic analysis showed that ∼87% of genes altered during bail-out induction recovered from stress status, suggesting resumption of metabolism, cell division, and immunity, while in degenerated polyps, only ∼71% of genes recovered. Quantitative polymerase chain reaction data further demonstrated that genetic recovery of energy production, cell proliferation, and immune response was achieved in morphologically recovered polyps within 3 days after bail-out, but was not fully accomplished in degenerated polyps even after 5 days. Our findings indicate that solitary polyps generated by hyperosmosis-induced bail-out can recover rapidly from physiological stress under laboratory conditions, suggesting that bailed-out polyps could be used as new models for coral research.